Development of a recombinase-aided isothermal amplification method coupled with a lateral flow dipstick assay for the diagnosis of powdery scab in potatoes - Yang, Jiahui; Li, Honghao; Wang, Yajie; Tang, Yingqing; Lan, Fengqi; Sun, Yue; Shao, Huanhuan; Cheng, Xiaojie; He, Xinyi; Liu, Dongyan; Jiang, Yusong; Yong, Bin; et al. (Frontiers in Microbiology, 2026)
Potato powdery scab is a soilborne disease caused by the fungus Spongospora subterranea, which belongs to the class of Plasmodiophorids and cannot be cultured. In this study, a species-specific genomic DNA fragment of Spongospora subterranea (2494 bp) was identified using comparative genomics methods. Polymerase chain reaction (PCR) and recombinase-aided amplification-lateral flow dipstick (RAA-LFD) base assays were then developed for the specific detection of this pathogen. Both detection methods effectively distinguished Spongospora subterranea from other common potato pathogens, and Polymyxa graminis and Plasmodiophora brassicae, the primary pathogens of the intercropping cruciferous and gramineous plants. The detection sensitivity of the three PCR primer pairs (SsF1/R1, SsF2/R2, and SsF3/R3) under the optimal conditions (60.5 °C; 40 cycles in a 20 μL reaction system) were 10.8 copies, 10.3 copies, and 10.6 copies, respectively. Using amplification durations of 10, 15, 20, and 25 min, the detection limits of the RAA primer and probe set (RS1F1/RI and RS1-Probe) in a 25 μL optimal reaction system were 2.51 × 103, 2.51 × 102, 2.51 × 102, and 2.51 × 101 copies, respectively. The PCR assays positively detected Spongospora subterranea DNA in all diseased tubers (41/41) and most samples of infested soil (27, 28, and 25 out of 31, corresponding to SsF1/R1, SsF2/R2, and SsF3/R3), whereas the RAA-LFD assay positively detected the pathogen in all tuber and soil samples when amplified at 37 °C for 20 min. The RAA-LFD outperformed PCR specifically in soil samples, mentioning performance metrics. The RAA-LFD isothermal detection assay developed herein provides a rapid, specific, and field-deployable method for diagnosing potato powdery scab in tubers and soil.